Financial sector development and economic growth: a co-integration analysis for ASEAN countries - Farooq, Rana Muhammad Adeel; Abu Bakar, Nor'Aznin; Raji, Jimoh Olajide (Inderscience Enterprises Ltd., 2020)
Among the 17 sustainable development goals (SDGs) of the United Nation, the 8th goal emphasises economic growth as an essential means of achieving other SDGs especially in developing countries. Therefore, this study empirically investigates the role of financial sector development, among other relevant factors, in the economic growth of five ASEAN economies over the 1994-2017 period. It uses Kao and Fisher-Johansen co-integration tests to examine the presence of a long-run association among the variables. Furthermore, FMOLS method is used to determine the long-run estimates of the predictors' influences on the economic growth of those countries. The long-run outcomes of the estimation suggest that financial sector development and human development index have significant positive impact on the economic growth of those countries. Based on the findings, this study recommends ASEAN countries to embrace additional robust measures to improve the financial sector and human development in order to realise sustainable economic growth.